Embedding aligned nanofibrous architectures within 3D-printed polycaprolactone scaffolds for directed cellular infiltration and tissue regeneration - Zijie Meng; Xingdou Mu; Jiankang He; Juliang Zhang; Rui Ling; Dichen Li (International Journal of Extreme Manufacturing, 2023)
Three-dimensional (3D) printing provides a promising way to fabricate biodegradable scaffolds with designer architectures for the regeneration of various tissues. However, the existing 3D-printed scaffolds commonly suffer from weak cell-scaffold interactions and insufficient cell organizations due to the limited resolution of the 3D-printed features. Here, composite scaffolds with mechanically-robust frameworks and aligned nanofibrous architectures are presented and hybrid manufactured by combining techniques of 3D printing, electrospinning, and unidirectional freeze-casting. It was found that the composite scaffolds provided volume-stable environments and enabled directed cellular infiltration for tissue regeneration. In particular, the nanofibrous architectures with aligned micropores served as artificial extracellular matrix materials and improved the attachment, proliferation, and infiltration of cells. The proposed scaffolds can also support the adipogenic maturation of adipose-derived stem cells (ADSCs) in vitro . Moreover, the composite scaffolds were found to guide directed tissue infiltration and promote nearby neovascularization when implanted into a subcutaneous model of rats, and the addition of ADSCs further enhanced their adipogenic potential. The presented hybrid manufacturing strategy might provide a promising way to produce additional topological cues within 3D-printed scaffolds for better tissue regeneration.